Relationship between heart rate variability and acute:chronic load ratio throughout a season in NCAA D1 men's soccer players - Sekiguchi, Y.; Huggins, R. A.; Curtis, R. M.; Benjamin, C. L.; Adams, W. M.; Looney, D. P.; West, C. A.; Casa, D. J. (The Journal of Strength and Conditioning Research, 2021)
The purpose of this study was twofold: (a) to examine the relationship between heart rate variability (HRV) and acute:chronic workload ratio (ACWR)-based training load (TL) metrics and (b) to examine relationships across various A:C ratio-based TL metrics. Heart rate variability in 23 male college soccer players (mean ± SD; age, 21 ± 1 years; body mass, 80.3 ± 5.8 kg; height, 181.9 ± 6.5 cm; %body fat, 11.9 ± 2.0%; and VO2max, 51.9 ± 5.0 ml/kg/min) was measured at 5 time points: week(W)1, W3, W7, W12, and W14 during the 2015 NCAA men's soccer season. Heart rate variability was calculated from beat to beat intervals using a heart rate monitor. Players donned a global position satellite-enabled device that measured the following TL metrics: session time (ST), Player Load (PL), PL/min, and total distance (TD). Acute:chronic workload ratio was calculated for each TL metric: ACWR-based ST (ACWRST), ACWR-based PL (ACWRPL), ACWR-based PL·min-1 (ACWRPLM), and ACWR-based TD (ACWRTD): ACWR = week average TLs/mo average (30 ± 1 days) TLs. Relationships between HRV and ACWR-based each TL metric were evaluated using mixed effects models. Tukey pairwise comparisons were used to examine differences between types of ACWR-based TL metrics. An increase in ACWRST significantly reduced HRV throughout a season (-7.4 ± 3.6 m/s; p = 0.04). There were significant differences between ACWRPLM and ACWRST, ACWRPL and ACWRTD at W1, ACWRPLM and ACWRST at W3 (p < 0.05). In conclusion, ACWRST, ACWRPL, and ACWRTD were significantly different from ACWRPLM. ACWRST was found to significantly predict HRV; higher ACWRST was significantly associated with lower HRV. Therefore, tracking of the ACWR using ST may help to optimize athlete's physiological state throughout a season.